Anterior lingual mandibular bone cavity: a case report - Pintado-Palomino, Karen; Tirapelli, Camila; Almeida, Luciana Yamamoto; Santos, Jessica Luana dos; Teixeira, Lucas Ribeiro; Ferraz, Emanuela Prado; Xavier, Samuel Porfirio; León, Jorge Esquiche (Brazilian Dental Science, 2020)
Stafne’s bone cavity (SBC) is an asymptomatic lingual bone cavity situated near the angle of the mandible. The anterior variant of SBC, which shows a radiolucent unilateral ovoid lingual bone concavity in the canine-premolar mandibular region, is uncommon. A 73-year-old man was referred for assessment of loss of mandibular bone. Panoramic radiographs and computerized tomography scans showed a well-defined lingual bony defect in the anterior mandible. Analysis of imaginological documentation, made 14 years ago, revealed a progressive increase in mesiodistal diameter and intraosseous bony defect. The soft tissue obtained within the bony defect, microscopically revealed fibrous stroma containing blood vessels of varied caliber. The current anterior lingual mandibular bone defect case is probably caused by the salivary gland entrapped or pressure resorption, which can explain the SBC pathogenesis. KEYWORDS Bone defect; Mandible; Cone beam computed tomography; Diagnosis; Case report.